The Influence of Zakat, Infak, and Sedekah on Poverty through Per Capita Income - Ekawaty, Marlina (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2025)
This study explores the relationship between zakat distribution and per capita income across Indonesian provinces in 2023. Drawing on secondary data from BAZNAS and official national statistics, the findings reveal an unexpected negative association between zakat distribution and income levels, suggesting that regions receiving higher zakat allocations tend to have lower per capita income. This outcome contrasts with the theoretical expectation that zakat, whether distributed for consumptive or productive purposes, should contribute to income growth through increased household spending or business capital. Further analysis indicates that zakat’s role as an economic empowerment instrument remains limited, as a considerable portion of its distribution is directed toward non-economic sectors. These findings highlight the need for a more strategic approach to zakat allocation, particularly by strengthening its focus on productive economic programs, skill development, business mentoring, and systematic impact evaluations. Such measures are expected to enhance zakat’s contribution to poverty alleviation and support a more inclusive income growth.